1969
DOI: 10.1002/jlac.19697230109
|View full text |Cite
|
Sign up to set email alerts
|

Komplexchemisches Verhalten von Acetylenen, II1)Indeno‐indene aus Schwermetallkomplexen von 1.2‐Bis‐phenyläthinyl‐benzol

Abstract: In unserer ersten Mitteilung 1) berichteten wir uber Darstellung und einige Eigenschaften der PalIadium(I1)-und Platin(1V)-Komplexe des 1.2-Bis-phenylathiny1-benzols (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, all of the compounds are, depending on the size of the π‐system, intensely colored. The color and the UV/Vis spectra of the targets, together with the results obtained for the previously reported compounds 2 c , and 2 b , are given in Figures and . The color of the compounds red shifts (Figure ) when going from 2 c to 4 b ( in film as well as in solution).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, all of the compounds are, depending on the size of the π‐system, intensely colored. The color and the UV/Vis spectra of the targets, together with the results obtained for the previously reported compounds 2 c , and 2 b , are given in Figures and . The color of the compounds red shifts (Figure ) when going from 2 c to 4 b ( in film as well as in solution).…”
Section: Resultsmentioning
confidence: 98%
“…Figure shows the packing of all of the synthesized compounds and also of 2 b and 2 c , the synthesis of which had been reported earlier. Compounds 2 c and 2 b pack in a herringbone motif along the longitudinal axis of the molecules. The closest measured contact between individual atoms belonging to two different layers of this arrangement was measured to be 3.5 Å for 2 c , 2 b and 2 a .…”
Section: Resultsmentioning
confidence: 99%
“…In early studies, the key starting compound was 1,2-bis(phenylethynyl)benzene (29a), treatment of which with PtCl 4 in benzene afforded a Pt-complex of dibenzopentalene 1bb, an unstable compound that converted to 1bb during purification (Scheme 15) [36,37]. The yield of 1bb was 85%.…”
Section: Preparation Of Dibenzopentalenes In the Presence Of Catalystsmentioning
confidence: 99%
“…[1] A variety of synthetic entries to this class of compounds has been described, including classical group transformation chemistry, [2,3] radical coupling, [4,5] and metal-induced reactions. [6][7][8][9][10] We have now found that dibenzopentalenes can be formed by B(C 6 F 5 ) 3 -induced intramolecular alkynyl coupling reactions.…”
mentioning
confidence: 99%
“…The products were separated by chromatography and each product was characterized by X-ray diffraction and by spectroscopy (for details see the Supporting Information). The compounds 4 a [10] and 4 b were identified as the dibenzopentalene derivatives (for example, 4 b: pentalene CH: d = 6.44 ppm ( 1 H NMR), d = 126.1 ppm ( 13 C NMR); see the Supporting Information). The compounds 5 a and 5 b contain the same dibenzopentalene framework as 4, but in addition to Scheme 1.…”
mentioning
confidence: 99%